2014
DOI: 10.1371/journal.pone.0094168
|View full text |Cite
|
Sign up to set email alerts
|

Brucella melitensis in France: Persistence in Wildlife and Probable Spillover from Alpine Ibex to Domestic Animals

Abstract: Bovine brucellosis is a major zoonosis, mainly caused by Brucella abortus, more rarely by Brucella melitensis. France has been bovine brucellosis officially-free since 2005 with no cases reported in domestic/wild ruminants since 2003. In 2012, bovine and autochthonous human cases due to B. melitensis biovar 3 (Bmel3) occurred in the French Alps. Epidemiological investigations implemented in wild and domestic ruminants evidenced a high seroprevalence (>45%) in Alpine ibex (Capra ibex); no cases were disclosed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 34 publications
2
63
0
2
Order By: Relevance
“…France, bovine brucellosis officially free since 2005 with no cases reported in domestic/wild ruminants since 2003, reported isolations of B. melitensis from wild mountain goats (Alpine ibex or Capra ibex). Previously, Mick et al (2014) reported on the risk of transmission to livestock and spill over of B. melitensis from wildlife to domestic ruminants and the sustainability of infection in Alpine ibex in a well-delineated mountain area in the French Alps. To get insight into brucellosis in dogs in Europe, the database in Germany of a veterinary diagnostic laboratory which received samples from dogs for B. canis testing from 20 European countries, was investigated (2011-2016) (Buhmann et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…France, bovine brucellosis officially free since 2005 with no cases reported in domestic/wild ruminants since 2003, reported isolations of B. melitensis from wild mountain goats (Alpine ibex or Capra ibex). Previously, Mick et al (2014) reported on the risk of transmission to livestock and spill over of B. melitensis from wildlife to domestic ruminants and the sustainability of infection in Alpine ibex in a well-delineated mountain area in the French Alps. To get insight into brucellosis in dogs in Europe, the database in Germany of a veterinary diagnostic laboratory which received samples from dogs for B. canis testing from 20 European countries, was investigated (2011-2016) (Buhmann et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…can spill over into livestock and humans. In France, B. melitensis has been isolated from an Alpine ibex (Capra ibex) and has probably spilled over to cattle and from cattle to humans (110). In Argentina, B. suis has been isolated in armadillos (Chaetophractus villosus), but spillover from armadillos to livestock and humans has not yet been reported (111).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Molecular characterization of circulating strains of Brucella is critical for elimination of repeated outbreaks, tracking infection spread, and informing selection of anti-brucellosis strategies [15, 16]. Multiple-Locus Variable-number tandem-repeat Analysis (MLVA) is a well-suited technique for genotyping of Brucella [17–19].…”
Section: Introductionmentioning
confidence: 99%